Faith-Based Women’s Organization Philanthropy in Fighting against the COVID-19 pandemic and Its Impacts: The Case of Aisyiyah in Sidoarjo, Indonesia - Hazim, Hazim; Fihayati, Zuyyina (UIN Sunan Gunung Djati Bandung, 2022)
Since the emergence of the global COVID-19 pandemic, faith-based philanthropic activities have become widely attractive topics to be investigated. Yet, there has been little exploration related to gender issues. This study examined faith-based women’s engagement in dealing with the COVID-19 outbreak and its impacts focusing on a local context in Sidoarjo, Indonesia. Notably, the investigation aimed to explore the extent to which Aisyiyah's philanthropy in addressing the global issue. To achieve the purpose of the study, it carried out a qualitative method incorporating three data collection techniques: semi-structured interview involving 17 informants; participant observation focused on Aisyiyah’s programs conducted to overcome the COVID-19; and a desk study gained from documents, reports, media (and social media) such as Facebook, Twitter, and YouTube channels. The result delineates that while some scholars divide two paradigms of community engagement which are utilitarian and social justice, Aisyiyah in Sidoarjo has played vital contributions oriented toward social justice. This approach has been done through various programs; public awareness building, embracing the COVID-19 patients, and enhancing social solidarity to reduce the outbreak effects. These findings contribute to filling the literature gap on religious-based women's philanthropy in dealing with the pandemic. However, it is critical to explore the extent to which Aisyiyah's commitment to humanitarian activities for a long-term period since no one can even predict when it will end. Another pivotal issue that needs further investigation is Aisyiyah’s way in mobilizing social capital to support its philanthropic activities.